1981
DOI: 10.1346/ccmn.1981.0290202
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Poorly Crystalline Hydrated Aluminous Goethites

Abstract: Abstraet--AI-substituted goethites were prepared by rapid oxidation of mixed FeCI2-AICI 3 solutions at pH 6.8 in the presence of CO2 at 25~ A combination of AI substitution and adsorption of CO2 reduced crystal size (except for an increase at small additions of AI) and produced unusual thin, porous particles. Product goethites had surface areas up to 283 mZ/g and unit-cell expansions induced by hydration. Substitution of AI for Fe reduced the 111 spacing and increased infrared OH-bending vibrational frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
45
1
3

Year Published

1983
1983
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 31 publications
12
45
1
3
Order By: Relevance
“…Peak maxima coincide with a maximum rate of weight-loss, whereas the minima between peaks occur during the transition between weight-loss events. Multiple weight-loss events immediately preceding bulk dehydroxylation are attributed to dehydration or dehydroxylation of surface Fe (oxo)hydroxo functional groups and similar events were observed in several investigations with goethites of varying crystallinity (Paterson and Swaffield, 1980;Fey and Dixon, 1981;Mackenzie et al, 1981;Schulze and Schwertmann, 1984;Schwertmann, 1984b;Schulze and Schwertmann, 1987;Gasser et al, 1996). In this study, all goethites showed this complex weight-loss pattern to varying degrees as illustrated by thermograms for samples prepared in the absence of Mn or Pb and aged at different pH and temperature ( Figure 2).…”
Section: Morphology and Surface Dehydrationdehydroxylationsupporting
confidence: 84%
“…Peak maxima coincide with a maximum rate of weight-loss, whereas the minima between peaks occur during the transition between weight-loss events. Multiple weight-loss events immediately preceding bulk dehydroxylation are attributed to dehydration or dehydroxylation of surface Fe (oxo)hydroxo functional groups and similar events were observed in several investigations with goethites of varying crystallinity (Paterson and Swaffield, 1980;Fey and Dixon, 1981;Mackenzie et al, 1981;Schulze and Schwertmann, 1984;Schwertmann, 1984b;Schulze and Schwertmann, 1987;Gasser et al, 1996). In this study, all goethites showed this complex weight-loss pattern to varying degrees as illustrated by thermograms for samples prepared in the absence of Mn or Pb and aged at different pH and temperature ( Figure 2).…”
Section: Morphology and Surface Dehydrationdehydroxylationsupporting
confidence: 84%
“…Note, however, that the strong goethite-excluding effect of A1 does not occur in soils, probably because goethite is formed by oxidation of Fe(II). For example, in synthesis experiments using Fe(II) as the Fe source, goethite was the only phase at room temperature (RT) and pH 7, even at high R~ (-0.4 mol mo1-1) (Taylor and Schwertmann, 1978;Goodman and Lewis, 1981;Fey and Dixon, 1981).…”
Section: Minerals Formedmentioning
confidence: 99%
“…Rendon and Serna (1981) and Serna et al (1982) showed that morphological variations may also be a major cause of spectral differences in the case of microcrystalline materials. Fey and Dixon (1981), in fact, noted that differing degrees of structural hydration may lead to shifts in the 900-cm -~ band of goethite. J6nfis and Solymfir (1970) used a third preparative method so that it seems likely that the three different sets of results shown in Figure 3 may be due to variations in the degree of structural hydration and/ or morphology resulting from the mode of preparation.…”
Section: Aluminous Goethitesmentioning
confidence: 99%
“…This conclusion is supported by the present results--a band at 460 cm was noted only for the three highest A1 concentrations (see Figure 6), and can in fact be attributed to a-Al203 (Farmer, 1974). De Grave et al (1982) recently detected corundum in the X-ray powder diffraction pattern of 15 mole % Al-substituted hematite after the sample was heated to 900~ Thus, FTIR analysis may indicate the extent of solid solubility in some mineral systems, despite previous assertions to the contrary (Tarte, 1968;Fey and Dixon, 1981).…”
Section: Aluminous Hematitesmentioning
confidence: 99%
See 1 more Smart Citation